Burrow architecture of the Damaraland mole-rat (Fukomys damarensis) from South Africa. Issue 1 (2nd January 2016) - Thomas, Hannah G; Swanepoel, Daniel; Bennett, Nigel C
Abstract : The burrow architecture (length, internal dimensions, fractal dimension of tunnel systems, number of nesting chambers and surface mounds) was investigated in the Damaraland mole-rat ( Fukomys damarensis ). A total of 31 animals were caught from five different colonies and their burrow systems were excavated in their entirety. The mean and SD colony size was 6 ± 3.3, with a range of 2–10 mole-rats. The sex ratio tended to be male biased 1.21:1. Males had a body mass of 80.5 ± 33.8 g, but were not significantly different to those of females, which had a mean body mass of 83.4 ± 24.9 g. The burrow system of the Damaraland mole-rats follows the same general architectural plan as recorded for other species of mole-rat with either one or two more centrally based, deeper, more permanent burrows that often connect to a nest area, which is used for resting and rearing offspring. The burrow systems contained several more superficial secondary tunnels at a shallower depth. The secondary tunnels accounted for up to 80% of the total burrow system. The mean length of the burrow system was 130 m and covered an area of 1 403 m 2 . The mean number of secondary branches in a burrow system was 10. The mean fractal dimension was 1.15, which implies the mole-rats do not explore their surrounding environment particularly efficiently when compared with that of other mole-rat species, but this may relate to the size of the main food resource, the Eland bean ( Elephantorrhiza elephantina ), which is randomly distributed and fed on in situ . Our study showed that colony size influences the size and complexity of the burrow system, with larger colonies having a longer burrow system covering a greater area with more secondary tunnels than that of smaller colonies.